General Principles of Medical Treatment - Clay, Jordan L.; Youssefi, Julie L.; Bensalem-Owen, Meriem K. (Seminars in Neurology, 2025)
Seizures are paroxysmal neurological events that are encountered by all medical specialties. Seizures are common, with 1 in 10 people experiencing a seizure at some point in their life. Furthermore, recurring unprovoked seizures are the hallmark of the condition of epilepsy, which encompasses a spectrum of syndromes that can occur across the lifespan. Although individual seizures may be brief occurrences, they are disruptive to an individual's activities of daily living (ADLs), increase the risk of physical injury, and adversely impact the mental well-being of those who experience them. Thus, in order to provide the best management, it falls into a clinician's domain to be informed of the types of seizures along with possible provoking factors and risks of recurrence, and when to make a diagnosis of epilepsy. Attention will be given to treatment of epilepsy with medications, characteristics that may impact management, and situations that require advanced specialty care.
Keywords: seizure; epilepsy; seizure classification; epilepsy management; antiseizure medications